IDDF2018-ABS-0061 Risk of tuberculosis in inflammatory bowel disease and other immune-mediated diseases on biological therapy: a population-based study in hong kong. (June 2018) - Wang, Xing; Wong, Sunny; Wang, Xian-Song; Tang, Whitney; Wu, Bin; Wu, Justin; Chan, Francis; Sung, Joseph; Ng, Siew
Abstract : Background: Biological therapies are increasingly used to treat inflammatory bowel disease (IBD) and other immune-mediated diseases. However, real-world epidemiological data on the risk of tuberculosis (TB) in these patients are scarce. We investigated the incidence of TB in patients with immune-mediated diseases in a population-based setting and stratified the risk of TB among different biologics. Methods: Data on patient demographics, disease diagnosis, types of biologics and TB infections were collected from a territory-wide computerised database of patient records managed by the Hong Kong Hospital Authority. We calculated the incidence rates (IRs) of TB infections in subjects treated with different biologics between 2006 and 2015, and reported standardised incidence ratio (SIR) by comparing with the general population. Subgroup analyses were performed based on the types of immune-mediated diseases and biologic drugs. Results: A total of 2485 patients with immune-mediated diseases were identified (10.6% IBD, 77.7% rheumatology, and 11.8% dermatology). 54 subjects developed active TB during 6921 person-years of follow-up. The mean age was 43 years, and the median follow up duration was 748 days. The overall SIR for TB in patients with included immune-mediated disease was 10.91. Patients with IBD had an over 17-fold increased risk of TB compared to the general population (SIR, 17.53), and patients on infliximab had a nearly 26-fold increased risk of TB compared to the general population (SIR, 25.95). Risk of TB was highest in the age group 50–59 years (SIR, 15.72). The risk of TB with infliximab was higher than etanercept (hazard ratio [HR], 4.10) and adalimumab (HR 2.08). No significant difference in the risk of TB was observed among the subgroups of IBD, rheumatology and dermatology. Conclusions: In the population-based study, biological therapy is associated with higher risk of TB in patients with immune-mediated diseases compared with the general population, and infliximab is associated with the highest risk of TB amongst all biologics. This study suggests patient and biologic selection may be important in balancing the benefit and risk of TB when treating patients with immune-mediated diseases.